1999
DOI: 10.1152/ajpheart.1999.276.5.h1691
|View full text |Cite
|
Sign up to set email alerts
|

Human sympathetic and vagal baroreflex responses to sequential nitroprusside and phenylephrine

Abstract: We evaluated a method of baroreflex testing involving sequential intravenous bolus injections of nitroprusside followed by phenylephrine and phenylephrine followed by nitroprusside in 18 healthy men and women, and we drew inferences regarding human sympathetic and vagal baroreflex mechanisms. We recorded the electrocardiogram, photoplethysmographic finger arterial pressure, and peroneal nerve muscle sympathetic activity. We then contrasted least squares linear regression slopes derived from the depressor (nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
333
2
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(359 citation statements)
references
References 36 publications
18
333
2
6
Order By: Relevance
“…1,[3][4][5][6][7]9,14,16,[18][19][20][21]27,31 The baroreflex sensitivity is different for blood pressure increases and reductions, which is evident by comparing phenylephrine with nitroprusside infusion, or neck pressure with neck suction methods. [18][19][20] Heart rate asymmetry, although independent of blood pressure asymmetry, is probably related to baroreflex, which is supported by the observation that heart rate asymmetry is correlated with measures of baroreflex function. 32 Porta et al 33 showed that asymmetrical features of HRV change during sympathetic provocation like head-up tilting and that heart rate asymmetry expression increases during the day compared with night, both in healthy people and patients with congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[3][4][5][6][7]9,14,16,[18][19][20][21]27,31 The baroreflex sensitivity is different for blood pressure increases and reductions, which is evident by comparing phenylephrine with nitroprusside infusion, or neck pressure with neck suction methods. [18][19][20] Heart rate asymmetry, although independent of blood pressure asymmetry, is probably related to baroreflex, which is supported by the observation that heart rate asymmetry is correlated with measures of baroreflex function. 32 Porta et al 33 showed that asymmetrical features of HRV change during sympathetic provocation like head-up tilting and that heart rate asymmetry expression increases during the day compared with night, both in healthy people and patients with congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most physiological and clinical studies continuous noninvasive recordings of blood pressure signal at the finger level are most commonly used. [4][5][6][7][8][9]14,[18][19][20][21]27,35 Studies on blood pressure asymmetry can develop in different directions. First, the explanation of the mechanisms responsible for this phenomenon like the influence of respiration, autonomic provocations or blockade is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs were administered via a catheter placed in an antecubital vein. After a 10-min baseline period, 100 g of sodium nitroprusside were administered, followed ϳ60 s later by 150 g of phenylephrine HCl (21). These doses decreased arterial pressure 10-15 mmHg below baseline levels and then increased blood pressure 5-10 mmHg above the baseline levels, respectively.…”
Section: Subjectsmentioning
confidence: 99%
“…The sensitivity of arterial baroreflex control of MSNA was identified from the linear relationship between MSNA and diastolic pressure during pharmacologically induced changes in blood pressure (11,21). Diastolic pressure was used because MSNA correlates closely with diastolic pressure but not with systolic pressure (23).…”
Section: Subjectsmentioning
confidence: 99%